Strategi pembangunan perdesaan berbasis lokal - Arsyad, Lincolin (Yogyakarta : UPP STIM YKPN, 2011)
Development of rural areas in Indonesia.
Includes bibliographical references (p. 107-109).
Keywords: Villages -- Indonesia; Indonesia -- Rural conditions